Transmedia intertextual systems: conceptual explorations and investigative approaches (2013)
This paper explores some of the theoretical discussions that are currently developing about Transmedia Storytelling as a concept, focusing on key notions such as Storytelling Expansion and Intertextual Relationships and ends by indicating the necessity of